2013
DOI: 10.1111/conl.12063
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Linked Social–Ecological Systems in Marine Protected Areas

Abstract: In view of current worldwide coral reef decline, and the shortcomings of traditional top-down management schemes of Marine Protected Areas (MPAs), decision makers and scientists face the important challenge of developing new approaches to generate effective conservation strategies. This study evaluates MPAs as linked social-ecological systems (SES) to inform better management by calculating indices for ecological health, social adaptive capacity, and the impact intensity of overfishing, pollution, and tourism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 47 publications
1
37
0
2
Order By: Relevance
“…Most species were sampled at various depths and different locations of the same area, a main difference with other sampled areas in the Caribbean. Other factors, such as the unique conditions of the Southwestern Caribbean reefs, e.g., high sediment loads coming from Cartagena Bay (Restrepo et al 2006, Velásquez et al 2011, López-Angarita et al 2013, could also be responsible for this divergent pattern. Finally, recent studies have shown that other microorganisms such as archaea and bacteria also play a key role in the ecological dynamics on coral communities (Ainsworth et al 2010, Kimes et al 2010, Littman et al 2010; however, we were not able to characterize this microbial community at the time.…”
Section: Discussionmentioning
confidence: 99%
“…Most species were sampled at various depths and different locations of the same area, a main difference with other sampled areas in the Caribbean. Other factors, such as the unique conditions of the Southwestern Caribbean reefs, e.g., high sediment loads coming from Cartagena Bay (Restrepo et al 2006, Velásquez et al 2011, López-Angarita et al 2013, could also be responsible for this divergent pattern. Finally, recent studies have shown that other microorganisms such as archaea and bacteria also play a key role in the ecological dynamics on coral communities (Ainsworth et al 2010, Kimes et al 2010, Littman et al 2010; however, we were not able to characterize this microbial community at the time.…”
Section: Discussionmentioning
confidence: 99%
“…Following conflict with industrial fishers, stakeholders in the Gulf of Tribugá established the "Regional District of Integrated Management Golfo de Tribugá-Cabo Corrientes" in 2014 (Díaz and Caro, 2016), introducing a spatial and temporal control over the activity of trawlers. The exclusion of the industrial shrimp trawler fleet from Tribugá may bring about a stock recovery, but the implications of a ban on gillnets for fisher communities with limited livelihood options and adaptive capacity are unknown, and likely to be variable (López Angarita et al, 2014;Tilley and López-Angarita, 2016). Furthermore, the ZEPA is also the result of financial investment to push fishing effort offshore and the development of fair trade style market chains between cooperatives and restaurants.…”
Section: Discussionmentioning
confidence: 99%
“…However, coastal deforestation persists in the region despite of the emplacement of protection mechanisms such as protected areas and national environmental policies (Box 1). Other noteworthy problems persist, such as the lack of resources for implementing new policies, weak institutional platforms, and the need for qualified personnel (López Angarita et al, 2014). In addition enforcement is often not effective (Alvarado et al, 2012;García, 2010;TNC, 2011).…”
Section: Prospects For the Mangroves Of The Etpmentioning
confidence: 99%